The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40710-015-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Electrical Resistivity Tomography Survey Correlated to Hydrogeological Data for Mapping Groundwater Salinization: A Case Study from a Multilayered Coastal Aquifer in Rhodope, Northeastern Greece

Abstract: A large scale two dimensional electrical resistivity survey was carried out to investigate groundwater salinization phenomena of a multilayered coastal aquifer in south Rhodope area, northeastern Greece. The electrical resistivity tomography (ERT) profiles, calibrated with lithological, physicochemical and geophysical log data, were used to demarcate the geometry of the aquifer system and characterize the extent of the interface between saline and freshwater in a coastal groundwater system, which has been subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…So it can be said that in the fourth trajectory contained a layer of salt water because the area is mostly swamp. In the area is in line with the research of Galazoulas et al (2015) that uses a resistivity zone showed the phenomenon of groundwater from coastal aquifers successfully illustrated by groundwater aquifer that is four major resistivity zones ranging in values between 0.1 and 150 Ωm at various depths and locations. A very low resistivity zone (0.1-5 Ωm) correlated with saline water saturated layers, a medium resistivity zone (5-15 Ωm) attributed to clays and silts, and two high resistivity zones generally representing freshwater saturated sediments of coarse grain size (15-40 Ωm) or alterations of thin marl and fine sand layers (40-150 Ωm).…”
Section: Results Of Discusionsupporting
confidence: 73%
“…So it can be said that in the fourth trajectory contained a layer of salt water because the area is mostly swamp. In the area is in line with the research of Galazoulas et al (2015) that uses a resistivity zone showed the phenomenon of groundwater from coastal aquifers successfully illustrated by groundwater aquifer that is four major resistivity zones ranging in values between 0.1 and 150 Ωm at various depths and locations. A very low resistivity zone (0.1-5 Ωm) correlated with saline water saturated layers, a medium resistivity zone (5-15 Ωm) attributed to clays and silts, and two high resistivity zones generally representing freshwater saturated sediments of coarse grain size (15-40 Ωm) or alterations of thin marl and fine sand layers (40-150 Ωm).…”
Section: Results Of Discusionsupporting
confidence: 73%
“…The electrical resistivity tomography (ERT) method was successfully applied to the spatial characterization of saltwater intrusion in coastal areas [12,[17][18][19][20], but has not yet been used to map thin freshwater lenses. ERT is especially useful wherever a network of boreholes, piezometers, and direct sampling of groundwater are available [21,22]. The point measurements are useful to calibrate the ERT method that is then used to create a series of two-dimensional images of freshwater-saltwater distribution in the aquifer [19].…”
Section: Introductionmentioning
confidence: 99%
“…La resistividad de las rocas del subsuelo está relacionada con diversos parámetros: los minerales contenidos, la porosidad, el fluido que rellena los poros, el grado de saturación de agua de la roca, la salinidad del fluido, la temperatura, etc. Ejemplos de estudios previos en los que se aplicó este método en estudios hidrogeológicos se pueden encontrar en Ball et al (2010), Ratnakumari et al (2012), Galazoulas et al (2015); en casos de vertederos y detección de cavidades en Meads et al (2003), Chamberst et al (2006), Martínez-Pagan et al (2013) y Martínez-Moreno et al (2013; en zonas kársticas en Zhou et al (2002). Además, el casi inexistente impacto que esta técnica produce sobre el terreno hace de ella una opción muy recomendable para investigar el subsuelo de zonas protegidas con fines científicos o medioambientales.…”
Section: Introductionunclassified